Study of the 4p2, 5p2 and 5s5f excited configurations of the Zn and Cd isoelectronic sequences, using relativistic and non-relativistic semiempirical approaches - Di Rocco , Héctor Oscar (2016)
The consistency of the energy levels published for configurations 4p2, 5p2 and 5s5f belonging to Zn and Cd isoelectronic sequences is studied. Different semiempirical approaches considering the linearity of the Slater integrals for large Zc, the smoothness of the sF screening parameters, the energy values in terms of Z (or Zc), and the differences of the Ecalc−Eexp values are used, where Ecalc values are energies calculated with a Hartree-Hock method with relativistic corrections and superposition of configurations (HFR-SOC), and Eexp are the experimental values. For the np2 configurations both LS and relativistic jj expressions are considered. Configuration 5s5f is also analyzed taking into account the Land´e’s interval rule.